Endoscopic resection of gastric subepithelial lesions: techniques and tips - Michael Lajin, MD; Fateh Bazerbachi, MD; Helen Sohn, MD; Octavio Armas, MD (VideoGIE)
Background and Aims: In the past, endoscopic resection of gastric subepithelial lesions (SELs) was restricted to small lesions confined to the submucosa. Larger and deeper lesions were resected surgically. Recent innovations in endoscopy have yielded multiple techniques for extending the boundaries and providing minimally invasive resection of larger and deeper lesions. Methods: This article presents the different endoscopic modalities for resecting gastric SELs. The video illustrates, through clinical examples, how to choose the appropriate resection method and provides technical tips for these techniques. Results: In this case series, we implemented different endoscopic resection modalities on the basis of endoscopic and endosonographic evaluation of the tumor and patient anatomical factors. Successful en bloc resection of gastric SELs was achieved in all patients without adverse events. Conclusions: Multiple techniques made endoscopic resection of larger and deeper gastric SELs feasible. Successful resection requires familiarity with these techniques' tips and tricks.